A Campaign Design to Increase Interest in Traditional Snacks Among Youth Aged 16–20 in Jakarta - Tanesha, Princella; Mores, Harry (Universitas Multimedia Nusantara, 2025)
Globalization has reshaped snacking habits of Jakarta’s youth, with international snacks dominating social media and daily consumption. Meanwhile, traditional Indonesian snacks are losing appeal due to limited visibility and outdated representation. This study explores how digital media can re-engage youth with traditional snacks through the Design Thinking approach (Empathize, Define, Ideate, Prototype, Test). Qualitative methods such as interviews, questionnaires, and observations with respondents aged 16-20 in Jakarta were used to understand perceptions and preferences. Findings show that young consumer are drawn to humorous and visually dynamic snack content. Traditional snacks can regain appeal when presented with currently relevant trends and storytelling. Based on these insights, a social media campaign titled “Jadoel Still Cool” was developed and tested through short illustrated video, showing improved awareness and positive attitudes toward traditional snacks. This study demonstrates how human-centered design and digital storytelling can help preserve Indonesia’s culinary heritage amidst globalization-driven food trends. Keywords: traditional snacks; social media campaign; illustrated video; visual communication.